ANALISIS WACANA SARA MILLS DALAM FILM ANIMASI ISLAM “HIJRAH NISA” (ANALISIS AKUN YOUTUBE CISFORM UIN SUNAN KALIJAGA) - Erna Kurniawati (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
The meaning and understanding of Hijrah is still a human problem in today's era, many who support hijrah are struggles and battles in the way of Allah by taking up arms, but on the other hand there are also those who improve hijrah is a place to move from place to place and there is also another meaning often pronounced is hijrah is an action to go away. On the other hand, the meaning of emigration is often equated with jihad in the sense of taking up arms to preach or spread the religion of Islam, the compilation of preaching objectives is not appropriate by trying and teaching. Islamic animated film